COMMUNITY STRUCTURE AND DIVERSITY OF BUTTERFLIES IN TOLIPIR NATIONAL PARK, AZAD JAMMU AND KASHMIR (AJK) PAKISTAN - A. H. Faiz; F-I-Abbas; Z. Ali; L. Zahra (Journal of Animal and Plant Sciences, 2015)
Present study on Lepidopteran diversity was conducted over some 52 km of Tolipir National Park during summer, 2014 using line transects sampling method. A total of 20 butterfly species belonging to two Nymphalidae and Pieridae families were recorded. The Various diversity indices, i.e. Simpson Index (0.09), Shannon Winner Index (3.05), Berger- Parker Dominance Index (0.06), Margalef ’s Index (3.27), Menhinick Index (0.89), Buzas and Gibson's Index (0.96) were also calculated. The Lepidoptera diversity decreased along elevation gradient (1,400 – 2,600 m asl). This study will help in understanding the total energy flow in the ecosystem and in ensuring the soil fertility of Tolipir National Park.
Keywords: Biodiversity; Conservation; National parks; soil fertility